Cover Feature: Supported Iridium‐based Oxygen Evolution Reaction Electrocatalysts ‐ Recent Developments (ChemCatChem 20/2022). Issue 20 (5th October 2022) - Moriau, Leonard; Smiljanić, Milutin; Lončar, Anja; Hodnik, Nejc
Abstract : The Cover Feature portrays an iridium nanoparticle as a bird that is hesitant in choosing an appropriate nest among different options, which represent different electrocatalyst supports. The scene illustrates the necessity and difficulty to find a high surface area and electrically conductive Ir support material able to withstand the oxidative oxygen evolution reaction (OER) conditions in acidic media. In their Review, L. Moriau and co‐workers evaluate materials like carbon, ceramic, metal carbides and their different composites. The effect or interaction of the support with the Ir nanoparticles′ performances is critically discussed and the reasons for an enhancement in activity and stability are highlighted. Finally, future research directions and challenges in finding adequate OER support are presented. More information can be found in the Review by L. Moriau and co‐workers.